The Role of Dairy Cattle Husbandry in Supporting The Development of National Dairy Industry - Anneke Anggraeni; Sofjan Iskandar (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2008)
An intensive development in Indonesian dairy industry has expanded over two decades. During this period, the structure of the national dairy industry has progressed completely. The capacity of the national fresh milk production, however, has been able to supply only 35% of domestic milk demand. The milk domestic demand is predicted to be continous due to the increases in the national population and their welfare. Raising temperate dairy breed (Holstein-Friesian) under tropical climate has resulted many deteriorates in productivity. More inferiority has been found under a semi-intensive management at small dairy farms. The existence of various changes in the global trade regulation for agriculture commodities has been a considerable factor directly affecting the future development of the national dairy industry. Increasing efficiency of various determinant components of the national dairy industry is required to produce domestic fresh milk in a good quality at a competitive price. This paper is dealing with the status of various determined factors especially for dairy livestock components to improve the future national dairy industry prospectively, involving for the national dairy cattle population, domestic milk yield, productivity of dairy cattle, breeding system and supporting reproduction technology. More over, other essential factors providing for dairy institution as well as distribution and marketing domestic milk production are also described.   Key words: Dairy cattle husbandry, small dairy farms, national dairy industry